Conception And Construction Of An Electric Bike - Prakash, Vodnala Veda; Kumar, Algot Kiran; Raj, Kuna Naresh (International Journal of Psychosocial Rehabilitation, 2025)
The electric bicycle is a device that is electrically assisted and was created to supply electromagnetic momentums to an existing bicycle. As a result, the rider is relieved of the responsibility of creating the energy necessary to make the bicycle function properly. It has a powerful motor and sufficient battery power that just has to be charged in order to assist in hill climbing, create better driving speeds, and provide totally free electric transportation. It is our duty to cut down on the use of fuel and the byproducts of its combustion that are harmful to the environment. Taking all of this into mind, it is a baby step in the direction of lowering the usage of cars that use more fuel and drawing people's attention to alternatives to these kinds of transportation, such as electric bikes. Therefore, we propose to create a bike that is powered by an alternate source and named a battery-operated bike. This bike would reduce the amount of work required by a human rider.